The Global Meningococcal Initiative meeting on prevention of meningococcal disease worldwide: Epidemiology, surveillance, hypervirulent strains, antibiotic resistance and high-risk populations. (2nd January 2019) - Acevedo, Reinaldo; Bai, Xilian; Borrow, Ray; Caugant, Dominique A.; Carlos, Josefina; Ceyhan, Mehmet; Christensen, Hannah; Climent, Yanet; De Wals, Philippe; Dinleyici, Ener Cagri; Echaniz-Aviles, Gabriela; Hakawi, Ahmed; et al.
ABSTRACT: Introduction : The 2018 Global Meningococcal Initiative (GMI) meeting focused on evolving invasive meningococcal disease (IMD) epidemiology, surveillance, and protection strategies worldwide, with emphasis on emerging antibiotic resistance and protection of high-risk populations. The GMI is comprised of a multidisciplinary group of scientists and clinicians representing institutions from several continents. Areas covered : Given that the incidence and prevalence of IMD continually varies both geographically and temporally, and surveillance systems differ worldwide, the true burden of IMD remains unknown. Genomic alterations may increase the epidemic potential of meningococcal strains. Vaccination and (to a lesser extent) antimicrobial prophylaxis are the mainstays of IMD prevention. Experiences from across the globe advocate the use of conjugate vaccines, with promising evidence growing for protein vaccines. Multivalent vaccines can broaden protection against IMD. Application of protection strategies to high-risk groups, including individuals with asplenia, complement deficiencies and human immunodeficiency virus, laboratory workers, persons receiving eculizumab, and men who have sex with men, as well as attendees at mass gatherings, may prevent outbreaks. There was, however, evidence that reduced susceptibility to antibiotics was increasing worldwide. Expert commentary : The current GMI global recommendations were reinforced, with several other global initiatives underway to support IMD protection and prevention.